The Implementation of Community Learning Activity Center (PKBM) Program for Correctional Inmates at Class IIA Cibinong Correctional Facility - Prakoso, Ario Dwi; Purwaningsih, Prihatini; Hartini, Sri (Universitas Ibn Khaldun Bogor, 2025)
This study examines the implementation of the Community Learning Activity Center (PKBM) program for correctional inmates at the Class IIA Cibinong Correctional Facility. The study aims to explore the program's execution, its challenges, and possible solutions. Utilizing an empirical juridical approach, this research gathers data through observation and in-depth interviews. The findings highlight the significance of PKBM in improving the education and skills of inmates, the barriers faced during implementation, and the strategies employed to overcome them. Additionally, this study underscores the broader implications of inmate education for national development and crime prevention efforts.